2018
DOI: 10.1063/1.5016866
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of the quantum Hall effect in films of the three-dimensional Dirac semimetal Cd3As2

Abstract: Low-temperature magnetotransport studies are reported for (112)Cd3As2 films grown on (111)CdTe by molecular beam epitaxy as a function of the Cd3As2 film thickness. All films show Shubnikov-de Haas oscillations. An even-integer quantum Hall effect is observed for films thinner than 70 nm. For the thinnest films, the bulk is gapped and transport at low temperatures occurs only via the gapless, two-dimensional states. The lowest Landau level is reached at ∼10 T, and the longitudinal resistance nearly vanishes at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 28 publications
4
54
0
1
Order By: Relevance
“…Because they are required by the Z 2 invariant [7], surface states exist even when a band gap opens in the bulk, in analogy with 3D topological insulators [8]. Experimentally, it has been shown that the transport properties of thin Cd 3 As 2 films become increasingly dominated by 2D states as their thickness is decreased [9,10], eventually giving rise to a quantum Hall effect [9][10][11][12]. These 2D states have been shown to exhibit characteristics of 2D Dirac fermions, including a zero-energy Landau level [13].…”
Section: Introductionmentioning
confidence: 99%
“…Because they are required by the Z 2 invariant [7], surface states exist even when a band gap opens in the bulk, in analogy with 3D topological insulators [8]. Experimentally, it has been shown that the transport properties of thin Cd 3 As 2 films become increasingly dominated by 2D states as their thickness is decreased [9,10], eventually giving rise to a quantum Hall effect [9][10][11][12]. These 2D states have been shown to exhibit characteristics of 2D Dirac fermions, including a zero-energy Landau level [13].…”
Section: Introductionmentioning
confidence: 99%
“…Стоит отметить, что роль поверхностных состояний растет при уменьшении одного из характерных размеров системы (толщины), приводя к появлению у системы новых свойств. В недавней работе было показано, что для пленок Cd 3 As 2 толщиной менее 70 нм, выращенных на подложках CdTe методом молекулярно-лучевой эпитаксии, уже при ∼ 10 Тл наблюдается квантовый эффект Холла [12]. Это дает нам надежду обнаружить аналогичные эффекты при дальнейших исследованиях в сильных полях.…”
Section: Introductionunclassified
“…For example, while there is no bandgap in the bulk material, the Dirac nodes become gapped in thin (<60 nm) Cd 3 As 2 films. [8][9][10] Even if the bulk is gapped, however, Cd 3 As 2 still possesses surface states that are inherent to the topological invariant. 1 In previous low-temperature transport studies, the two-dimensional Dirac nature of these surface states was demonstrated.…”
mentioning
confidence: 99%
“…1 In previous low-temperature transport studies, the two-dimensional Dirac nature of these surface states was demonstrated. [8][9][10] In thin films, an electric field applied via a top gate is therefore expected to mostly modulate the carriers in the surface states. In the present study, we demonstrate FETs using thin, (112)-oriented Cd 3 As 2 channels.…”
mentioning
confidence: 99%
See 1 more Smart Citation